A quantitative LumiFluo assay to test inhibitory compounds blocking p53 degradation induced by human papillomavirus oncoprotein E6 in living cells - Giulio Nannetti (Scientific Reports, 2018)
High-risk human papillomaviruses (HR-HPVs) are the causative agents for the onset of several epithelial cancers in humans. The deregulated expression of the viral oncoproteins E6 and E7 is the driving force sustaining the progression of malignant transformation in pre-neoplastic lesions. Targeting the viral E6 oncoprotein through inhibitory compounds can counteract the survival of cancer cells due to the reactivation of p53-mediated pathways and represents an intriguing strategy to treat HPV-associated neoplasias. Here, we describe the development of a quantitative and easy-to-perform assay to monitor the E6-mediated degradation of p53 in living cells to be used for small-molecule testing. This assay allows to unbiasedly determine whether a compound can protect p53 from the E6-mediated degradation in cells, through a simple 3-step protocol. We validated the assay by testing two small molecules, SAHA and RITA, reported to impair the E6-mediated p53 degradation. Interestingly, we observed that only SAHA efficiently rescued p53, while RITA could not provide the same degree of protection. The possibility to specifically and quantitatively monitor the ability of a selected compound to rescue p53 in a cellular context through our LumiFluo assay could represent an important step towards the successful development of anti-HPV drugs.